In vitro age dependent response of macrophages to micro and nano titanium dioxide particles. Issue 2 (23rd April 2014) - Bruno, Marcos E.; Sittner, Maximiliano; Cabrini, Rómulo L.; Guglielmotti, María B.; Olmedo, Daniel G.; Tasat, Deborah R.
Abstract: As a result of corrosion, microparticles (MP) and/or nanoparticles (NP) can be released from the metallic implants surface into the bioenvironment. The biological response to these particles depends not only on the physico‐chemical properties of the particles but also on host factors, such as age. Macrophages have attracted wide concern in biomedicine. The aim of this investigation was to study the age related biological response of macrophages to TiO2 ‐MP and NP in vitro . Alveolar macrophages (AM) obtained from young and senescent rats were cultured and exposed to TiO2 ‐MP and NP. Cell metabolism, superoxide anion (O2 − ) and nitric oxide (NO) generation, and cytokine release (IL‐6, TNFα, IL‐10) were measured. Cell metabolism was not affected by particle exposure. O2 − and NO generation increased in a dose dependent manner. A marked increase on IL‐6 release was found in the young‐AM subpopulation exposed to TiO2 ‐MP. Conversely, both particle sizes induced a dose dependent release of TNFα in senescent‐AM. Only the highest concentration of TiO2 ‐particles caused a significant increase in IL‐10 release in AM‐cultures. These observations lend strong support to the suggestion that cellular response of macrophages to TiO2 ‐particles is age dependent. The biological effect of the particles would seem to be more deleterious in the senescent age‐group. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 471–478, 2015.